Case for local forest management: environmental services, internalisation of costs and markets - Nathan, Dev; Kelkar, Govind (2001)
The paper argues that forests are not only sources of timber and non-timber forest products, but also of environmental services. It is through the fall in the supply of local environmental services, like nutrient recycling and soil formation, that forest communities bear the external costs that are not included in the price of timber and other forest products. Local environmental services are taken into account in forest management decisions by local communities, but not by external agents, like forest departments, and form a basis for setting up local forest management systems. In arguing for the establishment of forest communities' property rights over forests, the paper supports the establishment of markets for regional and global environmental services provided by forests. - Reproduced
Keywords: Environment; Forest management